A Small RLSA Antenna Utilizing the Specification of Back Fires 17 dBi LAN Antennas - Teddy Purnamirza; Prayoga Budikesuma; Imran M. Bin Ibrahim; Depriwana Rahmi; Rika Susanti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This research developed a small RLSA antenna that mimics the specification of a Wi-Fi antenna that is available in markets, which is a Back Fires 17 dBi LAN antenna. This research used the size of the back fires antenna as the size for the RLSA antenna. Base on this size, we designed and simulated 71 RLSA antenna models. Among them, we chose a best model and fabricated its prototype. We measured the prototype and found that the measurement result fits the simulation result, thus verifying the correctness of the antenna model. Furthermore, we analysed that with the same size, our RLSA antenna has better performance compared to the back fires antenna, in term of gain (0,53 dB higher), and in term of bandwidth (1075 MHz wider). We also found that our RLSA antenna is lighter and thinner compared to the back fires antenna. We also test the RLSA antenna in real condition for indoor and outdoor communication link. The test showed that the RLSA antenna can performs properly.